Governance and Bank Valuation - Caprio, Gerard (World Bank, Washington, D.C., 2013)
Which public policies and ownership structures enhance the governance of banks? The authors construct a new database on the ownership of banks internationally and then assess the ramifications of ownership, shareholder protection laws, and supervisory and regulatory policies on bank valuations. Except in a few countries with very strong shareholder protection laws, banks are not widely held, but rather families or the state tend to control banks. The authors find that: (i) Larger cash flow rights by the controlling owner boosts valuations; (ii) Stronger shareholder protection laws increase valuations; and (iii) Greater cash flow rights mitigate the adverse effects of weak shareholder protection laws on bank valuations. These results are consistent with the views that expropriation of minority shareholders is important internationally, that laws can restrain this expropriation, and concentrated cash flow rights represent an important mechanism for governing banks. Finally, the evidence does not support the view that empowering official supervisory and regulatory agencies will increase the market valuation of banks.